A Double Dissociation in Sensitivity to Verb and Noun Semantics Across Cortical Networks. (15th February 2019) - Elli, Giulia V; Lane, Connor; Bedny, Marina
Abstract: What is the neural organization of the mental lexicon? Previous research suggests that partially distinct cortical networks are active during verb and noun processing, but what information do these networks represent? We used multivoxel pattern analysis (MVPA) to investigate whether these networks are sensitive to lexicosemantic distinctions among verbs and among nouns and, if so, whether they are more sensitive to distinctions among words in their preferred grammatical class. Participants heard 4 types of verbs (light emission, sound emission, hand-related actions, mouth-related actions) and 4 types of nouns (birds, mammals, manmade places, natural places). As previously shown, the left posterior middle temporal gyrus (LMTG+), and inferior frontal gyrus (LIFG) responded more to verbs, whereas the inferior parietal lobule (LIP), precuneus (LPC), and inferior temporal (LIT) cortex responded more to nouns. MVPA revealed a double-dissociation in lexicosemantic sensitivity: classification was more accurate among verbs than nouns in the LMTG+, and among nouns than verbs in the LIP, LPC, and LIT. However, classification was similar for verbs and nouns in the LIFG, and above chance for the nonpreferred category in all regions. These results suggest that the lexicosemantic information about verbs and nouns is represented in partially nonoverlapping networks.